A review of spiral wound membrane modules and processes for groundwater treatment - Tabi, Rita Namoe; Boakye, Patrick; Agyemang, Frank Ofori; Nxumalo, Edward Ndumiso; Oduro-Kwarteng, Sampson (Frontiers in Membrane Science and Technology, 2024)
The demand for freshwater keeps increasing on a global scale, and on the other hand, the availability of freshwater keeps diminishing. Groundwater has been identified as the largest source of freshwater that is readily accessible. Although the water is available for abstraction, it must be treated to meet application standards. Membrane processes are the options that industry and researchers are turning to for the purification of groundwater. This review provides an insight into the use of pressure-driven membrane processes for groundwater treatment, with focus on the spiral wound membrane module. A brief description of what a spiral wound module is and the plant set-up in which it is used is given. The various applications of the spiral wound module with regards to groundwater treatment have been reviewed. The shortcomings and challenges limiting the application of spiral wound modules and by extension, the treatment plant itself have been highlighted. To cap it all, the opportunities that can be exploited to overcome these challenges and position pressure-driven membrane processes for groundwater treatment as the go-to purification method have been discussed.